2017
DOI: 10.1080/10669817.2017.1283767
|View full text |Cite
|
Sign up to set email alerts
|

Directional preference of the wrist: a preliminary investigation

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 15 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…Classification in the extremities is determined based on the patient's response to repeated end range movement testing into one of 4 main syndromes; Derangement, Dysfunction, Postural, or Other, which includes referral of symptoms from the spine [7] (see Table 1). Prevalence of the Derangement syndrome in peripheral joints has been reported from 40-79% in the literature [8][9][10][11]. A systematic review reported acceptable inter-rater reliability of MDT assessment in the peripheral joints [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classification in the extremities is determined based on the patient's response to repeated end range movement testing into one of 4 main syndromes; Derangement, Dysfunction, Postural, or Other, which includes referral of symptoms from the spine [7] (see Table 1). Prevalence of the Derangement syndrome in peripheral joints has been reported from 40-79% in the literature [8][9][10][11]. A systematic review reported acceptable inter-rater reliability of MDT assessment in the peripheral joints [12].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of a suspected Derangement seeks to identify a direction of preference, a physiological movement that results in rapidly improved pain and movement. The directional preference movement is then used as an intervention for the patient's condition, leading to favorable patient outcomes [7][8][9]11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of MDT syndromes in peripheral joints includes the following: a survey finding 64% of 388 consecutive patients fitting an MDT syndrome [16], a randomized controlled trial finding 40% of 99 patients with knee OA awaiting total knee replacement surgery to be classified as Derangement syndrome [6], a case series finding 79% of 19 consecutive wrist patients classified as Derangement syndrome [17], and an observational study with 88.2% of 93 shoulder patients fitting an MDT classification [18]. A systematic review of six studies found the inter-rater reliability of MDT assessment to be acceptable between well-trained MDT clinicians in the spine and extremity joints [19].…”
Section: Introductionmentioning
confidence: 99%
“…In attempt to increase the ability and confidence of clinicians using MDT peripheral assessment, Maccio et al [17] examined the historical and physical characteristics of consecutive wrist patients, to determine association with directional preference. The most significant finding was an inverse relationship of excessive mechanical stress and directional preference in wrist Derangement syndrome (i.e.…”
Section: Introductionmentioning
confidence: 99%